Updating Health Literacy for Healthy People 2030: Defining Its Importance for a New Decade in Public Health. (November 2021) - Santana, Stephanie; Brach, Cindy; Harris, Linda; Ochiai, Emmeline; Blakey, Carter; Bevington, Frances; Kleinman, Dushanka; Pronk, Nico
Abstract : Content: Healthy People 2030, the fifth iteration of the Healthy People initiative, provides science-based national health objectives with targets to improve the health and well-being of Americans. For the first time since its 1979 establishment, the Healthy People framework aims to attain health literacy as an overarching goal and foundational principle to achieving health and well-being. Growing literature on health literacy describes it as a concept not solely reliant on individual capabilities but also on organizations' ability to make health-related information and services equitably accessible and comprehensible. Program: The US Department of Health and Human Services (HHS) updates the Healthy People objectives each decade based on the most current science. For the development of Healthy People 2030, HHS drew on recommendations from the Secretary's Advisory Committee on National Health Promotion and Disease Prevention Objectives for 2030 (Secretary's Advisory Committee), an independent advisory committee of national health experts, to update the 20-year old individual-focused Healthy People definition of health literacy. HHS solicited input from members of the public and users on the proposed changes to that definition. Implementation: HHS published a Federal Register notice to solicit public comments, which were qualitatively analyzed by government staff. Evaluation: The 2 separate analyses revealed plurality support for improving the definition to focus on both individual and organizational roles in health literacy. Results led HHS subject matter experts to update the definition to include definitions of personal health literacy and organizational health literacy. Healthy People 2030's expanded health literacy definition reflects the most current science and input from the Secretary's Advisory Committee, public comments, and HHS subject matter experts. Discussion: The updated definition is intended to advance Healthy People 2030's health literacy goals particularly as more organizations in public health and other sectors acknowledge their role in the delivery of quality health information and services.